Analysis of " One Village One Product" (OVOP) or "Satu Daerah Satu Industri (SDSI)" in Kelantan. - Abdul Aziz Ab Latif (Universiti Malaysia Kelantan, 2009)
The purpose of the study was to determine the effectiveness of One Village, One Product or in Bahasa Malaysia, "Satu Daerah, Sati Industri (SDSI) policies. The study investigates the success factors of Small and Medium Enterprises (SMEs) start-up and evaluation of SDSI policies, to clarify the business behavior and operational problems of rural base SDSI firms, and study on the effectiveness of SDSI and its relevancy in the state of Kelantan. In additional, this study analyzed the background of SDSI firms and entrepreneurs, their business condition and prospects, the evaluation of SDSI policy, and its future direction.